Strategi Berkelanjutan dengan Pendekatan Interpretive Structural Modeling (ISM) Kondisi Pandemi Covid 19 pada UKM Furniture - Jaka Purnama; Zainal Arief; Nur Rizka Athirah; Lingardi Wiratama (Journal of Research and Technology, 2022)
During the Covid-19 pandemic, furniture SMEs need to carry out a sustainable strategy analysis to maintain the continuity of SME activities. The limited sales made by furniture SMEs, due to the Covid 19 pandemic, hampered the sale of furniture products. Jombang furniture SMEs are business actors who process teak wood from forest products into furniture products that can provide added value. SME furniture is one of the leading products of Jombang district. Efforts to optimize the potential of existing resources, it is necessary to manage a sustainable supply chain strategy. Integrated strategic management in a sustainable manner based on economic, social and environmental aspects. The evaluation method used for the strategy formulation model is the Interpretative Structural Modeling (ISM) approach which is influenced by internal and external factors. Based on the economic, social and environmental elements, an alternative decision is taken that can be used in carrying out the business of producing furniture from each element. Implementation of activities must refer to government programs in the context of preventing the Covid 19 virus by imposing restrictions on community activities by not collecting mass in a place that will facilitate the spread of the Covid 19 virus. Sales strategy during the Covid 19 virus pandemic conditions by selling online, in accordance with government guidelines.